Characterization of landfill leachate molecular composition using ultrahigh resolution mass spectrometry. Issue 7 (22nd May 2021) - Martin, Katherine R.; Robey, Nicole M.; Ma, Shirley; Powers, Leanne C.; Heyes, Andrew; Schmitt-Kopplin, Philippe; Cooper, William J.; Townsend, Timothy G.; Gonsior, Michael
Abstract : Landfill leachate organic matter was molecularly characterized by FT-ICR-MS, revealing a significant and previously unidentified organochlorine signature. Abstract : Landfill leachate (LL) is a complex wastewater and an important potential source of environmental contamination. LL can contain high concentrations of ammonia, metals, other inorganic species, and dissolved organic carbon; however, bulk composition of dissolved LL organic matter (LLOM) is poorly understood. A better understanding of LLOM composition will inform treatment development and improve LL pollution tracing. In this study, we addressed this need for compositional and treatment information by characterizing LL from an active bioreactor municipal solid waste (MSW) landfill as well as from a closed MSW landfill. Through non-targeted ultrahigh resolution Fourier transform ion cyclotron resonance mass spectrometry (FT-ICR-MS) we were able to assign chemical formulas to thousands of singly charged molecular ions and compare samples to natural dissolved organic matter (DOM). LLOM was differentiated by a higher presence of sulfur-, nitrogen-, and chlorine-, particularly nitrogen–sulfur-, containing formulas. The abundance of chlorine-containing molecular formulas supports the existence of a non-volatile organochlorine component in MSW LL. We performed tandem MS (MS-MS) analyses to tentatively identify the presence of the flame retardant, chlorendic acid, and likely related compounds. Additionally, we measured contaminants of emerging concern (CECs) and other chemical parameters to further characterize LLs and found evidence suggesting a significant percent of Fe may be bound in Fe–organic complexes.